2015
DOI: 10.1128/jvi.02363-14
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ATP Citrate Lyase by mTOR Signal Induces Disturbed Lipid Metabolism in Hepatitis B Virus Pre-S2 Mutant Tumorigenesis

Abstract: The development of hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC) has been found to be associated with disturbed lipid metabolism. To elucidate the role of lipid metabolism in HBV tumorigenesis, we investigated the dynamic pattern of lipid metabolism in HBV pre-S2 mutant-induced tumorigenesis. Lipid and gene expression profiles were analyzed in an in vitro culture system and in transgenic mouse livers harboring HBV pre-S2 mutant. The pre-S2 mutant transgenic livers showed a biphasic pattern of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 28 publications
2
40
0
1
Order By: Relevance
“…[86, 233] In addition, studies have shown that mutant L-HBsAg can activate mTOR signaling, [261263] ultimately causing increased lipogenesis. [262] …”
Section: Hbv and Hccmentioning
confidence: 99%
“…[86, 233] In addition, studies have shown that mutant L-HBsAg can activate mTOR signaling, [261263] ultimately causing increased lipogenesis. [262] …”
Section: Hbv and Hccmentioning
confidence: 99%
“…The first step towards FA synthesis is the conversion of citric acid into acetyl-CoA by direct phosphorylation of ACLY. Hepatitis B virus (HBV) and HCMV infections activate the expression of ACLY [38, 39], however the enzymatic activity of ACLY is not critical for virus-induced lipogenesis. Virus-infected cells can use glucose carbon for FA synthesis by ACLY from citrate generated in mitochondria and acetyl-CoA synthetase short-chain family member 2 (ACSS2) from acetate [40].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the mRNA expression of lipogenic enzymes in human HCC samples from ten patients were examined and found to be significantly elevated, including the ACL mRNA, compared with surrounding liver tissue that did not show cancer (Yahagi et al, 2005). Western blot analysis of thirty chronic HBV-infected HCC patients revealed that in twenty of these patients, the HCC tissues had increased levels of ACL enzyme protein compared with paired adjacent non-tumor liver tissue (Teng et al, 2015). There has been reports of activation of ACL activity in Hepatitis B virus transgenic mouse liver.…”
Section: Atp Citrate Lyase Activity In Hbv Infected Liver Cellsmentioning
confidence: 99%
“…There has been reports of activation of ACL activity in Hepatitis B virus transgenic mouse liver. In a recent study, Teng et al, 2015 reported that in livers of transgenic mice expressing the pre-S2 deletion mutant of the LS protein of HBV, the ATP citrate lyase gene (ACL) mRNA levels was upregulated in HCC tissues. Western blotting also revealed the presence of higher levels of the ACL enzyme protein compared with the non-transgenic livers.…”
Section: Atp Citrate Lyase Activity In Hbv Infected Liver Cellsmentioning
confidence: 99%
See 1 more Smart Citation